ANALYSIS OF THE EFFECT OF MOTHER'S WORK AND FAMILY INCOME ON STUNTING INCIDENCE IN TODDLERS - Ayu Mariska; Marniati Marniati; Itza Mulyani (RADJA PUBLIKA, 2022)
A Mother's work background and family income have a big influence on the incidence of stunting in toddlers.The problem in this study is the high incidence of stunting in children under five which can have a negative impact on human resources (SMD) in the future. The purpose of this study was to analyze the effect of a mother's work and family income on the incidence of stunting in toddlers.This research method is quantitative with a cross-sectional design. The population in this study was mothers who had 121 months of under-five children (0-59) months with a total sample of 57 people, which was carried out in January 2022 in Darul Hikmah sub-district, Aceh Jaya district, analyzed using univariate and bivariate which was then tested with the chi-square test.The results showed that there was a significant effect of mother's work and family income on the incidence of stunting in children under five as evidenced by the P-value < 0.05.The conclusion after the analysis was that there was an effect of a mother's work and family income on the incidence of stunting.Suggestions for health workers and other related parties to be more intense in providing socialization to mothers of toddlers in terms of preventing toddlers from stunting.